Nancy Drew and the Clue Crew. # 2, Secret sand sleuths - Kinney, Sarah (Keene, Carolyn. Nancy Drew and the clue crew, 2013)
Nancy Drew and her friends Bess and George investigate when they discover a cleaning woman being fired for destroying a sand painting.